PENERAPAN KONSEP EDU-TOURISM SEBAGAI SOLUSI ARSITEKTUR REGENERATIF PADA LAHAN PASCATAMBANG TIMAH DI BANGKA - Sanjaya, Joanne Valencia; Carina, Nina (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2025)
The widespread exploitation of tin mining in the Bangka Belitung region has led to severe environmental degradation. One of the main causes is the lack of reclamation of post-mining land, leaving behind abandoned mining residues such as tailings and water-filled pits (kolong). These areas are often utilized as tourist spots by local communities,  yet they provide little to no contribution to actual environmental restoration. This research aims to explore how post-tin mining land in Bangka can be designed using a regenerative architectural approach combined with the concept of edu-tourism, functioning both as an educational facility and a means of ecosystem recovery. The methods used is literature studies, site observations, precedent studies, and analysis of the socio-ecological needs of local communities to identify programmatic needs as the basis for designing the proposed facilities. The analytical process was carried out in three stages: (1) identifying the existing site conditions of the post-mining land and surrounding community activities; (2) assessing the regenerative potential of the land and the educational value of environmentally-based tourism; and (3) formulating a program that supports ecological, educational, and social functions. The findings indicate that integrating these concepts can help restore the ecosystem, regenerate degraded mining areas into productive spaces, and utilize tailings as economic and social resources for local communities. Furthermore, this approach presents a potential model for sustainable post-mining land management in similar regions. The novelty of this research lies in the integration of regenerative architecture and edu-tourism to transform former mining lands into ecologically productive and socially beneficial spaces. Keywords:  edu-tourism; kolong; post-mining land; regenerative architecture; tailing Abstrak Maraknya eksploitasi tambang timah yang terjadi di wilayah Bangka Belitung telah menyebabkan kerusakan lingkungan yang cukup parah. Salah satu penyebab utamanya adalah lahan pascatambang timah yang tidak direklamasi, sehingga meninggalkan jejak tambang berupa tailing dan kolong yang terbengkalai. Area-area ini kerap kali dimanfaatkan sebagai tempat wisata oleh masyarakat sekitar, namun belum memberikan kontribusi nyata terhadap pemulihan lingkungan. Penelitian ini bertujuan untuk mengeksplorasi bagaimana lahan pascatambang timah di Bangka dapat dirancang dengan pendekatan arsitektur regeneratif dan konsep edu-tourism, sehingga mampu berfungsi sebagai sarana edukasi sekaligus mendukung pemulihan ekosistem. Metode yang digunakan meliputi studi literatur, observasi lapangan, studi preseden, dan analisis kebutuhan sosial-ekologis masyarakat lokal, untuk mengidentifikasi kebutuhan program sebagai dasar dari fasilitas perancangan. Proses analisis dilakukan melalui tiga tahap: (1) identifikasi kondisi eksisting lahan pascatambang dan aktivitas masyarakat sekitar, (2) potensi regeneratif lahan serta nilai edukatif dari tempat wisata berbasis lingkungan, serta (3) perumusan program ruang yang mendukung fungsi ekologis, edukatif, dan sosial. Hasil penelitian menggambarkan bahwa penggabungan konsep ini mampu membantu memulihkan ekosistem, meregenerasi lahan tambang menjadi ruang produktif, serta memanfaatkan tailing sebagai potensi ekonomi dan sosial bagi masyarakat lokal. Selain itu, pendekatan ini dapat menjadi contoh pengelolaan lahan pascatambang untuk wilayah yang serupa. Kebaruan dari penelitian ini terletak pada integrasi arsitektur regeneratif dan edu-tourism untuk mentransformasi lahan eks tambang menjadi ruang yang produktif secara ekologis dan bermanfaat secara sosial.